Determinação de metais em matrizes oleosas por HR-CS AAS após extração induzida por quebra de emulsão - Adolfo, Franciéle Rovasi (2022)
Three methods based on extraction induced by emulsion breaking were developed for the extraction and determination of metals in asphalt and oilseeds by high-resolution continuum source atomic absorption spectrometry with graphite furnace atomization. The first method reports the extraction of Cr, Cu and Mn from asphalt through the formation and breaking of oil-in-water (O/W) emulsions. Under optimized conditions, the sample (0.05 g), diluted in toluene (1.5 mL) and mineral oil (0.5 mL), was mixed with 5 mL of the extractant solution (Triton X-100 3% w/v and HNO3 15% v/v). Breaking occurred by heating at 90°C (20 min). The extraction efficiency ranged from 88.6 for Cu to 104% for Mn. Mono-elemental determination was performed on the primary lines of the three analytes. The limits of detection (LOD) were 0.02, 0.01 and 7.11 μg g-1 for Cr, Cu and Mn, respectively. Precision, expressed as relative standard deviation (RSD), ranged from 1.0 for Cu to 9.1% for Cr. The performance of the proposed method was compared to procedures reported in the literature, including microwaveassisted acid digestion (MW-AD), ultrasound-assisted acid extraction (USE), emulsification (E), and direct dilution (DD). The methods with the best performance parameters for Cu were EIEB, MW-AD, USE and E. For Cr and Mn, the best results were obtained by EIEB, MW-AD and DD. The second method reports the extraction of Co, Fe and Ni from asphalt through the formation and breaking of water-in-oil (W/O) emulsions. Under optimized conditions, the sample (0.08 g), diluted in toluene (1.5 mL) and mineral oil (3.5 mL), was mixed with 2 mL of the extractant solution (40% HNO3 v/v and Triton-X -100 40% v/v). Breaking occurred by heating at 90°C (15 min). Extraction efficiency ranged from 101 for Co to 104% for Ni. Simultaneous determination was performed on the secondary lines of Co (352.685 nm), Fe (352.604 nm) and Ni (352.454 nm). LODs were 0.025, 0.450 and 0.225 ng g-1 for Co, Fe and Ni, respectively. RSD ranged from 0.1 for Ni to 7.2% for Co. The third method describes the extraction of Ba, Co, Fe and Ni from oilseeds through the formation and breaking of solid-oil-water (S/O/W) emulsions. Under optimized conditions, the sample (0.8 g) was mixed with 4 mL of the extractant solution (20% v/v HNO3 and 15% w/v Triton-X- 100). Breaking occurred by heating at 90 °C (4 min) followed by centrifugation. The extraction efficiency ranged from 94.9 for Ba to 110% for Fe. Simultaneous determination was performed at secondary lines of Ba (352.497 nm), Co, Fe and Ni. The LODs were 19.95, 0.012, 0.474 and 0.011 μg g-1 for Ba, Co, Fe and Ni, respectively. RSD ranged from 0.4 for Ni to 8.0% for Co. The three proposed methods are simple, fast and low cost. Thus, they can be considered excellent alternatives to conventional sample preparation methods.